TEAR FILM CHANGES FOLLOWING PHACOEMULSIFICATION SURGERY IN PRIMARY EYE CARE CENTER: Oral Presentation - Observational Study - Ophthalmologist - TRI WAHYU (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Dry eye disease (DED) is one of the most commonly encountered problem in daily ophthalmology practice. One of many risk factors for DED is cataract surgery. Cataract surgery is known to modify tear film and ocular surface through corneal incision and ocular toxicity of peri- and postoperative medications. The aim of this study is to analyze tear film before and after phacoemulsification in primary eye care facility by measuring tear break-up time (TBUT), fluorescein staining, Schirmer I test (ST-I), and ocular surface disease index (OSDI) score. Methods : This was a longitudinal observational study with prospective cohort design, which included patients diagnosed with senile cataract and underwent uncomplicated phacoemulsification surgery at primary eye care center Sawangan Eye Clinic within period of June to December 2022. Friedman, Wilcoxon, and Cochran tests were used to analyze the data. Results : Thirty nine eyes from 39 patients met the inclusion criteria and were followed up to 3-month postoperatively. Mean age of the patients was 61.1±10.54 years, which consited of 53.8% males and 46.2% females. Mean preoperative OSDI score, corneal staining, TBUT, and ST-I were 24.94±10.24, 1.38±1.99, 2.94±2.17, and 15.46±8.80 respectively; while 3-month postoperative, these parameters’ means were 11.22±13.15 (p=0.0001), 1.38±2.56 (p=0.118), 3.13±1.79 (p=0.192), and 13.31±9.45 (p=0.006) respectively. OSDI was the only parameter which showed statistically significant changes from preoperative to postoperative follow ups (p<0.05). Conclusion : Phacoemulsification did not alter corneal staining and TBUT significantly after 3 months postoperatively, even though both of these parameters' preoperative value were already lower; yet OSDI score improved over time after surgery.